(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Rice is a staple food for more than half of the global population, underscoring the importance of sustainably intensifying rice production systems to ensure food security. Conventional nutrient management practices often lead to inefficient nutrient use, environmental contamination, and soil degradation. This review synthesizes recent developments in next-generation nutrient management strategies designed to improve both rice productivity and soil quality. Specifically, it examines site-specific nutrient management, controlled-release fertilizers, integrated nutrient management, digital agriculture tools, microbial biofertilizers, and conservation agriculture practices. These approaches are evaluated for their potential to increase nitrogen use efficiency, minimize environmental impacts, enhance soil health, and sustain or boost yield potential. The review also addresses implementation challenges in various rice ecosystems and proposes a framework for context-specific adoption. Ultimately, it identifies future research priorities, emphasising the need for a comprehensive evaluation of these technologies across multiple growing seasons and diverse agroecological zones.